Implementasi Pemberian Reward Pada Mata Pelajaran Pendidikan Agama Islam di Sekolah Menengah Pertama Terpadu Pondok Pesantren Daarul Rahman Kecamatan Tempuling - Hatni, Hatni; Risnawati, Risnawati; Zulkifli, Zulkifli; Marina, Hatna (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2024)
This article aims to provide a concept regarding the implementation of giving rewards in Islamic religious education subjects at the Integrated Junior High School Daarul Rahman Islamic Boarding School, Tempuling District, considering that there are still many teachers who do not implement the implementation of giving rewards. So, a solution is needed to overcome this. The method used is the quantitative descriptive method. Observation results found that the implementation of giving rewards in Islamic Religious Education subjects at the Daarul Rahman Islamic Boarding School Integrated Junior High School, Tempuling District, reached 79.37% and was categorized as good, because it was located in the interval 61% - 80%. Factors that can influence the implementation of rewards in Islamic Religious Education subjects at the Integrated Junior High School Daarul Rahman Islamic Boarding School, Tempuling District are the methods used by teachers, student learning motivation and family environmental background.